Analisis Pemetaan Global Value Chain: Studi Kausus Film “Sonic the Hedgehog3” - tarigan, ellyna raissa; Seto Bayu Aji; Joey Michael FlauranceAndia; Adiasri Purbantina (Universitas Riau, 2026)
Abstract The Era of Globalization makes it easier for various countries to cooperate and this is used by countries to do business, including film industry players. The involvement across the country's geographical borders in film production can add value and interest that aims to steal global attention in film marketing. Sonic the Hedgehog 3 is a movie that is loved by various circles. The movie Sonic the Hedgehog 3 is included in the science fiction genre directed by Jeff Fowler. The Sonic film involves many actors and crews from various countries from pre-production, filming, post-production to promotion. This research analyzes the value chain of Sonic the Hedgehog 3 using De Voldere's concept. This concept is used to map the value chain stage in the Global Creative Value Chain which is divided into two main functions: Core function and Support function. The author uses a descriptive qualitative method to analyze the Sonic the Hedgehog 3 film. This writing will use industry report data and online sources related to the production process of Sonic the Hedgehog 3. In addition, the creation and post-production stages through mastering CGI with actors become the biggest added value in Sonic Film. The Sonic film also managed to become one of the 10th grossing films in 2024 and the highest grossing film in the Box Office franchise.